THE DESIGN OF GAS STATION TERMINAL SEARCH APPLICATION BY APPLYING THE METHOD OF TRAVELING SALESMAN PROBLEM - Dimastara, Rafa; Manurung, Hotler; Sembiring, Hermansyah (Yayasan Bina Internusa Mabarindo, 2024)
The increasing need for transportation is unavoidable. Moreover, the ability of the community to obtain or use transportation is increasing due to the increasing income of the community. The number of means of transportation makes the density of existing highways so that sometimes the streets often run out of fuel because they do not know the location of the nearest fuel filling. General fuel filling station (SPBU) is a distribution institution built on a plot of land and has a gas station facility with a design, design, and technical specifications that have been approved by Pertamina. Gas stations are used to distribute and market fuel and or other products using Pertamina trademarks and can be used for NFR (Non Fuel Retail) business management. If the transportation equipment runs out of fuel, of course, immediately look for the nearest gas station from the location of the rider. If the distance is far from the location, he will push his vehicle until he finds the Pertamina gas station signboard, the farther the distance the location, the vehicle will definitely be tired to push it. Seeing from the many means of Transportation circulating on the streets, the author wants to create a system application that can find out the location of the nearest Pertamina gas station using the application. Users who use the application just need to run the application and search for the nearest Pertamina gas station from its location to be faster in the process of searching for Pertamina gas stations to refuel. So that users who will run out of fuel can go directly to the location to refuel at the nearest Pertamina gas station from their location.